Effectiveness of Islamic Counseling with Dhikr in Reducing Public Speaking Anxiety among Eighth-Grade Students - Nurzakyah Almawaddah; Ira Suryani (Journal of General Education and Humanities, 2025)
This study aims to test the effectiveness of Islamic counseling with dhikr in reducing public speaking anxiety among eighth-grade students of IT An-Nafis Private Junior High School. The problem of public speaking anxiety experienced by students has the potential to disrupt their learning process and speaking skills development, necessitating appropriate intervention. This research employs a quantitative method with a one-group pretest-posttest pre-experimental design. The sample consists of eight students with high anxiety levels selected purposively from a population of 47 eighth-grade students. The intervention was conducted through four sessions of Islamic counseling that integrated dhikr. Data analysis using the Wilcoxon test with SPSS version 30 showed significantly decreased anxiety levels (p = 0.012). Before the intervention, all students (100%) experienced high anxiety, while after the intervention, 75% were in the low anxiety category and 25% in the moderate category. These findings indicate that Islamic counseling with dhikr is effective as a spiritual-psychological approach to reducing anxiety in public speaking among eighth-grade students.